Mixed charmonium-molecule interpretation for the y (3940) state - Albuquerque, R. M. [UNESP]; Dias, J. M.; Nielsen, M.; Zanetti, C. M. (IOP Publishing, 2015)
QCD sum rules are used to study the mass and the decay widths of the Y(3940) state. We assume that it can be described by a mixed charmonium-molecule scalar current with JPC = 0++. Using a mixing angle θ = (76.0±5.0)°, we obtain MY = (3.95±0.11) GeV, which is in good agreement with the experimental mass of the Y(3940) state. We also evaluate the decay width in the channels Y → J/ψω and Y → γγ obtaining the values ΓY → j/ψω ≈ (1.7± 0.6) MeV and ΓY→γγ ≈ (1.6 ± 1.3) KeV, respectively. We also study the decay process of this state into channels containing DD mesons in the final state.